Assessments of aphasia : Practices and challenges faced by Malaysian speech language therapists - Fatimah Hani Hassan; Pei, Whey Heng; Susheel Joginder Singh; Rahayu Mustaffa Kamal (Penerbit Universiti Kebangsaan Malaysia, 2023)
Aphasia assessment is crucial in diagnosing aphasia, determining the extent of language impairment, and identifying factors that may support or restrict aphasia recovery to design an appropriate plan of care for people with aphasia. Speech-language therapists (SLTs) play a major role in conducting aphasia assessments. Little is known about the practices of SLTs in assessing aphasia in low-resource regions. The present study aims to identify aphasia assessment practices among Malaysian SLTs and related challenges, as well as strategies for improving aphasia assessments from SLTs’ perspectives. A total of 32 SLT participants who have been practicing in Malaysia completed an online survey to gather their background information, data pertaining to practices and challenges in conducting aphasia assessments, and suggestions for improving aphasia assessments. Descriptive analyses were conducted for all numerical data. Suggestions for improving aphasia assessment practices were analysed qualitatively using the thematic content analysis approach. SLT practices in aphasia assessment were found to be consistent in certain aspects, but not all. Two major challenges were identified: (a) linguistic barriers between clinicians and clients/caregivers, and (b) a lack of standardized assessment tools for aphasia evaluations. Participants suggested “Internal Strategies” and “External Strategies” for improving aphasia assessment practices.